LAYANAN INFORMASI TENTANG SELF EFFICACY DAN OPTIMIS DALAM UPAYA MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK - Asni Asni; Arik S usiati (Universitas Borneo Tarakan, 2023)
AbstractThis study aims to increase the self-confidence of class VII SMPN 248 Jakarta students through information services about self-efficacy and optimism. The population of 128 students and researchers set certain criteria to be the subject of the study. The method used in this research uses a quantitative approach. The self-confidence instrument consists of 30 questions. In the pretest, the average self-efficacy component of class VII SMPN 248 Jakarta was 39%. Meanwhile, the average optimistic component of class VII SMPN Jakarta was 36%. This means that the average before the information service is carried out is categorized as low. After the information service is carried out, it is categorized as high. As the percentage of posttest components of self-efficacy, the average class VII SMPN 248 Jakarta is 69%. Meanwhile, the posttest for the optimistic component of class VII SMPN 248 Jakarta was 68%. So that it can be concluded that there is a significant increase in the self-confidence of class VII SMPN 248 Jakarta students on average by 37% in the self-efficacy component and by 32% in the optimistic component. The conclusion of this study is that information services can increase the self-confidence of class VII students at SMPN 248 Jakarta. Guidance and counseling teachers can implement information services to increase students' self-confidence.Kata Kunci: Self Afficaci, Kepercayaan DiriAbstrakPenelitian ini bertujuan untuk meningkatkan kepercayaan diri peserta didik kelas VII SMPN 248 Jakarta melalui layanan informasi tentang self efficacy dan optimis. Populasi sebanyak 128 peserta didik dan peneliti menetapkan kriteria tertentu yang menjadi subjek penelitian. Metode yang digunakan dalam penelitian menggunakan pendekatan kuantitatif. Instrumen kepercayaan diri yang berjumlah 30 butir soal. Pada pretest komponen self efficacy rata-rata kelas VII SMPN 248 Jakarta sebesar 39%. Sedangkan pretest komponen optimis rata-rata kelas VII SMPN 248 Jakarta sebesar 36%. Hal ini berarti rata-rata sebelum dilakukan layanan informasi dikategorikan rendah. Setelah dilakukan layanan informasi dikategorikan tinggi. Sebagaimana prosentase posttest komponen self efficacy rata-rata kelas VII SMPN 248 Jakarta sebesar 69%. Sedangkan posttest komponen optimis rata-rata kelas VII SMPN 248 Jakarta sebesar 68%. Sehingga dapat disimpulkan ada peningkatan yang signifikan kepercayaan diri peserta didik kelas VII SMPN 248 Jakarta rata-rata sebesar 37% pada komponen self efficacy dan sebesar 32% pada komponen optimis. Kesimpulan dari penelitian ini adalah layanan informasi dapat meningkatkan kepercayaan diri peserta didik kelas VII SMPN 248 Guru bimbingan dan konseling dapat mengimplementasikan layanan informasi untuk meningkatkan kepercayaan diri peserta didik.Keyword: Self Efficacy, Self Confidance